Drop-by-drop chemical reaction and sample introduction for capillary electrophoresis1. Issue 12 (21st June 2015) - Chen, Fengming; Rang, Ying; Weng, Ying; Lin, Luyao; Zeng, Hulie; Nakajim, Hizuru; Lin, Jin-Ming; Uchiyama, Katsumi
<x xml:space="preserve">Abstract</x> On-line microreaction and separation with the combination of drop-by-drop injection and capillary electrophoresis.